The Influence Of Budget Preparation Participation On The Performance Of The Bantaeng Regency Government Apparatus - Evi Nurul Husna; Wa Ode Rayyani; Amelia Rezki Septiani Amin (CV. AFDIFAL MAJU BERKAH, 2024)
The purpose of This research aims to analyze the influence of budget participation on the performance of government officials in Bantaeng Regency. This sample was taken from the Bantaeng Regency Regent's office, representing each SKPD. The type of data used in this research is quantitative data obtained from distributed questionnaires and is related to the problem being studied. In this research, the data sources used in data collection include primary data. The research instrument used in this research used a Likert scale. Based on the results of data research using statistical calculations through the Statistical Package for the Social Science (SPSS) version 26 application regarding the influence of budget preparation participation on the performance of Bantaeng Regency government officials, the research results showed that the variable participation in budget preparation had a regression coefficient in a positive direction. The significance test can be seen in the regression coefficient (β) and significance value (Sig.) obtained showing that sig α = 0.05>0.000, which means that there is an influence of budget preparation participation on the performance of government officials in Bantaeng Regency. Thus, it can be concluded that the better participation in budget preparation, the higher the government performance in Bantaeng Regency.